(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
In the ever-evolving landscape of education, the integration of technology has become a pivotal force, transforming the way we approach teaching and learning. Pedagogical technology, a term that encompasses the innovative tools, platforms, and strategies that enhance the educational experience, has emerged as a fundamental aspect of modern pedagogy. This article delves into the profound impact of pedagogical technology, exploring its multifaceted benefits, the challenges it presents, and the future implications for the educational landscape.